Formation of nanoemulsions in stirred media mills - Schmidt, Jochen; Damm, Cornelia; Romeis, Stefan; Peukert, Wolfgang (Chemical Engineering Science, 2013)
Alkane-Tween85-water-systems have been used as model emulsion systems to demonstrate the feasibility of emulsification in stirred media mills. The influence of fundamental process parameters, i.e. emulsion formulation (oil mass fraction and oil-to-emulsifier mass ratio), stress conditions (grinding bead size and stirrer tip speed), process time and especially temperature on the emulsion droplet size and size distribution has been studied for this approach. By lowering the process temperature below the solidification temperature of the oil phase, coalescence and ripening can be significantly reduced. Smallest product droplets with x<10nm thus are obtained even for nominal oil mass fractions up to 20wt% in the hexadecane-Tween85-water system. The feasibility of the process proposed to produce nanoscale emulsions using oil phases loaded with compounds such as pigments and other fillers is demonstrated. © 2013 Elsevier Ltd.
Keywords: Formulation; Nanoemulsion; Oil-in-water emulsion; Stirred media mill; Surfactant; Tween85